Genome-wide identification of kiwifruit K+ channel Shaker family members and their response to low-K+ stress - Yinqiang Zi; Zhiming Zhang; Ke Zhao; Xiuyao Yang; Ling Zhu; Tuo Yin; Chaoying Chen; Ke Wen; Xulin Li; Hanyao Zhang; Xiaozhen Liu (BMC Plant Biology, 2024)
Abstract Background ‘Hongyang’ kiwifruit (Actinidia chinensis cv ‘Hongyang’) is a high-quality variety of A. chinensis with the advantages of high yield, early ripening, and high stress tolerance. Studies have confirmed that the Shaker K+ genes family is involved in plant uptake and distribution of potassium (K+). Results Twenty-eight Shaker genes were identified and analyzed from the ‘Hongyang’ kiwifruit (A. chinensis cv ‘Hongyang’) genome. Subcellular localization results showed that more than one-third of the AcShaker genes were on the cell membrane. Phylogenetic analysis indicated that the AcShaker genes were divided into six subfamilies (I-VI). Conservative model, gene structure, and structural domain analyses showed that AcShaker genes of the same subfamily have similar sequence features and structure. The promoter cis-elements of the AcShaker genes were classified into hormone-associated cis-elements and environmentally stress-associated cis-elements. The results of chromosomal localization and duplicated gene analysis demonstrated that AcShaker genes were distributed on 18 chromosomes, and segmental duplication was the prime mode of gene duplication in the AcShaker family. GO enrichment analysis manifested that the ion-conducting pathway of the AcShaker family plays a crucial role in regulating plant growth and development and adversity stress. Compared with the transcriptome data of the control group, all AcShaker genes were expressed under low-K+stress, and the expression differences of three genes (AcShaker15, AcShaker17, and AcShaker22) were highly significant. The qRT-PCR results showed a high correlation with the transcriptome data, which indicated that these three differentially expressed genes could regulate low-K+ stress and reduce K+ damage in kiwifruit plants, thus improving the resistance to low-K+ stress. Comparison between the salt stress and control transcriptomic data revealed that the expression of AcShaker11 and AcShaker18 genes was significantly different and lower under salt stress, indicating that both genes could be involved in salt stress resistance in kiwifruit. Conclusion The results showed that 28 AcShaker genes were identified and all expressed under low K+ stress, among which AcShaker22 was differentially and significantly upregulated. The AcShaker22 gene can be used as a candidate gene to cultivate new varieties of kiwifruit resistant to low K+ and provide a reference for exploring more properties and functions of the AcShaker genes.